Optimization of rapid acquisition with relaxation enhancement (RARE) pulse sequence parameters for 19F‐MRI studies. Issue 1 (13th November 2013) - Mastropietro, Alfonso; De Bernardi, Elisabetta; Breschi, Gian Luca; Zucca, Ileana; Cametti, Massimo; Soffientini, Chiara Dolores; de Curtis, Marco; Terraneo, Giancarlo; Metrangolo, Pierangelo; Spreafico, Roberto; Resnati, Giuseppe; Baselli, Giuseppe
Abstract : Purpose: To optimize signal‐to‐noise ratio (SNR) in fast spin echo (rapid acquisition with relaxation enhancement [RARE]) sequences and to improve sensitivity in 19 F magnetic resonance imaging (MRI) on a 7T preclinical MRI system, based on a previous experimental evaluation of T1 and T2 actual relaxation times. Materials and Methods: Relative SNR changes were theoretically calculated at given relaxation times (T1, T2 ) and mapped in RARE parameter space (TR, number of echoes, flip back pulse), at fixed acquisition times. T1 and T2 of KPF6 phantom samples (solution, agar mixtures, ex vivo perfused brain) were measured and experimental SNR values were compared with simulations, at optimal and suboptimal RARE parameter values. Results: The optimized setting largely depended on T1, T2 times and the use of flip back pulse improved SNR up to 30% in case of low T1 /T2 ratios. Relaxation times in different conditions showed negligible changes in T1 (below 14%) and more evident changes in T2 (−95% from water solution to ex vivo brain). Experimental data confirmed theoretical forecasts, within an error margin always below 4.1% at SNR losses of ∼20% and below 8.8% at SNR losses of ∼40%. The optimized settings permitted a detection threshold at a concentration of 0.5 mM, corresponding to 6.22 × 10 16 fluorine atoms per voxel. Conclusion: Optimal settings according to measured relaxation times can significantly improve the sensitivity threshold in 19 F MRI studies. They were provided in a wide range of (T1, T2 ) values and experimentally validated showing good agreement.J. Magn. Reson. Imaging 2014;40:162–170 . ©2013 Wiley Periodicals, Inc .